X-ray diffraction pattern and relative crystallinity of irradiated arrowroot starch - Aline Gonçalves Barroso; RAFAEL HENRIQUE GARCIA; NÉLIDA LUCIA DEL MASTRO (Brazilian Journal of Radiation Sciences)
After cereals, tubers and roots are the major source of starch for food and industrial uses. Arrowroot refers to any plant of the genus Marantha, but the term is most commonly used to describe the easily digested starch obtained from the rhizomes of Marantha arundinacae. The rhizomes of this herbaceous plant contain about 20% of starch. As few studies exist on arrowroot starch, the objective of this preliminary work was to study the X-ray diffraction (XRD) patterns of arrowroot starch when treated by γ-radiation with doses up to 15 kGy in a 60Co source. The XRD patterns of the arrowroot starch exhibited A-type crystalline arrangements with strong peaks at approximately 15º, 17º, 18ºand 23º (2θ). A slight increase of diffractogram peaks intensity was noticed after the irradiation process. The cristallinity index was calculated using Bruker DIFFRAC.EVA version 4.2 software. Relative crystallinity seems to increase with radiation doses, and this effect is more noticeable at low doses. That can be attributed to different radiation sensitivity among the amorphous and crystalline regions of the arrowroot starch molecule. Present results will contribute to elucidate the behavior under radiation treatment of this starchy component increasingly employed by the food industry.